2007
DOI: 10.2166/wh.2007.011
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water microbiological survey of the Northwestern State of Sinaloa, Mexico

Abstract: A potable water survey, in two important municipalities of the state of Sinaloa, Mexico was conducted. Culiacan, capital city of Sinaloa and its neighboring municipality, Navolato were selected to enumerate Aeromonas hydrophila, Escherichia coli, fecal and total coliforms, Pseudomonas aeruginosa, and Heterotrophic plate count bacteria from 100 households' taps. Manganese; residual chlorine; pH; temperature and turbidity were also examined. Overall, Aeromonas hydrophila was not detected in any of the samples, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
6
6
1
Order By: Relevance
“…The incidence of Pseudomonas spp. as the third dominant bacteria in the current study was in agreement with report made elsewhere [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…The incidence of Pseudomonas spp. as the third dominant bacteria in the current study was in agreement with report made elsewhere [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, one hundred percent of tap water samples were found to be contaminated with heterotrophic bacteria. Similar rates of contamination were also found by Islam et al in Dhaka city [ 10 ] and Chaidez et al in Mexico [ 28 ]. But, slightly low rates of contamination were found by Anwar (91.3 %) in Punjab [ 29 ] and Nguendo-Yongsi et al (95 %) in Yaounde [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…Though slightly higher to present study, the recovery rate of thermotolerant Coliform was found low that is 19.6% (Aryal 2009) to 23.3% (Shrestha 2008). Chaidez et al (2008), detected 46% Total coliform and 26% faecal coliform in drinking water conducted in Mexico. The reason for such a high percentage of total coliform in drinking water may be due to the depletion of the residual chlorine through the pipeline and the water may gets contaminated due to leakage, rusty pipelines or sewage contamination.…”
Section: The Mean Free Residual Chlorine (Frc) Mean Combinedmentioning
confidence: 96%